7(z-5)+1=2-3(2z-1)

Simple and best practice solution for 7(z-5)+1=2-3(2z-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(z-5)+1=2-3(2z-1) equation:


7(z-5)+1=2-3(2z-1)

We simplify the equation to the form, which is simple to understand
7(z-5)+1=2-3(2z-1)

Reorder the terms in parentheses
+(+7z-35)+1=2-3*(2z-1)

Remove unnecessary parentheses
+7z-35+1=+2-3+*(+2z-1+)

Reorder the terms in parentheses
+7z-35+1=2+(-6z+3)

Remove unnecessary parentheses
+7z-35+1=+2-6z+3

We move all terms containing z to the left and all other terms to the right.
+7z+6z=+2+3+35-1

We simplify left and right side of the equation.
+13z=+39

We divide both sides of the equation by 13 to get z.
z=3

See similar equations:

| 2x+6x-14=22 | | [4x+4]=28 | | 12+x=-3x(4-x) | | 6(2x-5)=12 | | -118-3x=77+12x | | 12x+x=-3x(4-x) | | [-7x+4]=18 | | 2(6x+2)=-(2x-10) | | C=3ab | | (x+0.2)(x-0.2)= | | -11a-17a+11a+10a+-2a=18 | | 4x-37=x+35 | | 1/2+3/2=3 | | C=3pieab | | 20x-16=4x+ | | -9x+13=5 | | 18t-13t-t-3t=12 | | 3+2z-1=7z+7-42 | | 18-17x=-20.5 | | -82+6x=-2x+30 | | (4a+x)(a-x)= | | 16a-15a=15 | | (11x-3y)(2x+y)= | | 13=9+v/4 | | -2n=-3n+8 | | 257-63h= | | 2x+16=x-3 | | -3x+2=-6x+8 | | 2=-2x-4 | | z^2-5z+21=0 | | 90+90+(2+4)+(3x-29)=360 | | (9x+2)(x-3)= |

Equations solver categories